Commentary: systems biology approach to model the life cycle of Trypanosoma cruzi - Carrea, Alejandra (2017)
In a recent work we have identified, from a bigger gene regulatory network, a seven-node module involved in the control of the life cycle of Trypanosoma cruzi (T. cruzi) (Carrea and Diambra, 2016). To that end, we have analyzed microarray gene-expression data of the four different T. cruzi’s life cycle stages, by means of a systems biology approach.